Structural dynamics of earthquake engineering theory and application using Mathematica and MATLAB - Rajasekaran, Sundaramoorthy (CRC ; Woodhead, 2009)
Annotation This important book looks at how structural dynamics can be applied to earthquake engineering of structures in theory and practice. It will give practical examples of how Mathematica and Matlab can be used to model and predict the way in which structures will be affected by earthquakes. This vital area of modelling/simulation can help design buildings and civil engineering projects to withstand the effects of earthquakes. The book will give an introductory overview of structural dynamics and its importance in earthquake engineering, followed by an in-depth look at the different structural dynamic theories.
CRC Press order no.: N10026.
Keywords: MATLAB.; Earthquake engineering -- Mathematics.; Structural dynamics -- Mathematics.; Mathematica (Computer program language); elektronické knihy; electronic books